The deaf way II anthology : a literary collection by deaf and hard of hearing writers - Stremlau, Tonya M. (Gallaudet University Press, 2002)
In July 2002, the second Deaf Way Conference and Festival took place at Gallaudet University in Washington, D.C., attracting more than 5,000 people worldwide. Researchers, artists, performers, and others converged to create a singular blend of scholarship and social interaction, which inspired The Deaf Way II Anthology. The Deaf Way II Anthology brings together stellar contributions by 16 international writers who are deaf or hard of hearing. This remarkable collection features poetry, essays, short stories, and one play, all of which offer thought-provoking perspectives on elements from the personal universes of these gifted authors. Many are United States writers well-known for their past publications, such as Douglas Bullard, Willy Conley, Christopher Heuer, and Raymond Luczak, while the outstanding work of John Lee Clark, volume editor Tonya Stremlau, Melissa Whalen, and several others have been collected for the first time in this volume. The international contributions further distinguish this anthology, ranging from poetry by Romanian Carmen Cristiu, verse by Sibylle Gurtner May from Switzerland, to a play by Nigerian Sotonwa Opeoluwa. All of the writers showcased in The Deaf Way II Anthology portray the Deaf experience with unmatched authenticity, presenting a perfect introduction to the Deaf world. Simultaneously, their work demonstrates that deaf and hard of hearing people can write at the highest aesthetic level and offer invaluable insights on the complete human spectrum. Tonya M. Stremlau is an associate professor of English at Gallaudet University.